Gott in der Zeit - Schneider-Flume, Gunda (Zeitschrift für Theologie und Kirche, 2000)
Experience of God, of time, and of oneself are connected with each other. This connection is not to be understood within the frame of a metaphysical thought of god, but in the context of the realism of mercy: God's time is qualified by the movement of mercy. Discussing different theories of time (Augustin, M. Theunissen, U. Beck, E. Erikson) the character of time as a gift is elaborated and understood as a way of secular speaking of God.